Left upper lobectomy and systematic lymph nodes dissection in enlarged pulmonary hilar lymph nodes in primary lung cancer patient by uniportal video-assisted thoracic surgery - Fan, Jun-Qiang; Yao, Jie; Chang, Zhi-Bo; Wang, Qi (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Uniportal video-assisted thoracic surgery (VATS) anatomical pulmonary resection, with only one small incision for surgery instruments and camera insertion, requires higher operative skills, especially in the cases of the enlarged pulmonary hilar lymph nodes. With improved technology and increased experiences in VATS lobectomy, uniportal VATS lobectomy has been applied in major medical centers recently. A 67-year-old male patient with left upper peripheral lung cancer and enlarged hilar lymph nodes underwent unipotal VATS lobectomy and systemic mediastinal lymph node dissection. The patient recovered uneventfully.